PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA DOSEN DI UNIVERSITAS PAWYATAN DHAHA KEDIRI - Ita Yoeli Astari (Universitas Islam Kadiri, 2019)
The terms of leadership will be more directed at how to achieve organizational targets. Many styles of leadership within the organization, but the implementation of the right to be something that a propriety. In education, transformational leadership style will be better than other leadership styles. University Pawyatan Daha Kediri abbreviated UPD is an organization implementing transformational leadership style, an institution educational organization that can push all the elements, from lecturers, students, faculty / staff, parents, local communities and others to work. The problems in this research are: (1) How does the style of leadership transformational Against Labor productivity Lecturer at the University Pawiyatan Dhaha Kediri, (2) How does the ability Work on Productivity of work Lecturer at the University Pawiyatan Dhaha Kediri, (3) How big is the influence of leadership style transformational and ability to work on Productivity of work at the University Pawiyatan Dhaha Kediri. Based on the theoretical basis that has been stated above, then the hypothesis in this study is: